1997
DOI: 10.1046/j.1468-2982.1997.1705570.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow and Oxygen Metabolism during Migraine with and Without Aura

Abstract: Eleven cases of migraine with and without aura were investigated with positron emission tomography (PET). Regional cerebral blood flow (rCBF), oxygen metabolism (rCMRO2) and oxygen extraction (rOER) were measured during baseline (n = 11), aura (n = 6), headache (n = 10) and after treatment with sumatriptan (n = 4). Data were analysed using an ROI-based approach from 26 different anatomically defined regions, and also an exploratory approach whereby all subjects were normalized to a stereotactic brain atlas; t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 36 publications
4
32
1
5
Order By: Relevance
“…CSD is a wave of neuronal and glial depolarisation, followed by long-lasting suppression of neural activity, and it can be evoked in mammals with lissencephalic [63,64] or folded cortex [65]. Human neuroimaging such as planar Xenon [66][67][68][69], single photon emission tomography [68,[70][71][72][73][74] positron-emission tomography [75,76], magnetoencephalography [77,78] and MRI [79][80][81] support the hypothesis that CSD underlies migraine [82]. However many subjects never experience symptoms of typical visual auras in studies showing spreading hypoperfusion [75] or blood oxygenation level-dependent (BOLD) signal changes [79], and the initial hyperaemia characteristics of CSD were not directly demonstrated in human cortex.…”
Section: The Migraine Aura: Ascending To the Central Origin Of Migrainementioning
confidence: 99%
“…CSD is a wave of neuronal and glial depolarisation, followed by long-lasting suppression of neural activity, and it can be evoked in mammals with lissencephalic [63,64] or folded cortex [65]. Human neuroimaging such as planar Xenon [66][67][68][69], single photon emission tomography [68,[70][71][72][73][74] positron-emission tomography [75,76], magnetoencephalography [77,78] and MRI [79][80][81] support the hypothesis that CSD underlies migraine [82]. However many subjects never experience symptoms of typical visual auras in studies showing spreading hypoperfusion [75] or blood oxygenation level-dependent (BOLD) signal changes [79], and the initial hyperaemia characteristics of CSD were not directly demonstrated in human cortex.…”
Section: The Migraine Aura: Ascending To the Central Origin Of Migrainementioning
confidence: 99%
“…These include planar Xenon (6)(7)(8)(9), single photon emission tomography (8,(10)(11)(12)(13)(14), positron-emission tomography (15,16), magnetoencephalography (17,18), and MRI (19)(20)(21). Each demonstrated one or more aspects of CSD associated with migraine aura.…”
mentioning
confidence: 99%
“…Only one study using PositronEmission-Tomography (PET) performed during human migraine aura documented cortical regions corresponding to the visual cortex with significant reduction in CBF (-23% :oligaemia) and Cerebral Metabolic Rate of Oxygen (CMRO 2 ) (-22%) but no change in Oxygen Extraction Fraction (OEF) compared to baseline. These data suggest that cerebral ischemia is not the primary cause of the attacks in these cases [3].…”
Section: Introductionmentioning
confidence: 64%
“…In this study, a clear temporal and spatial correlation is established between the visual symptoms of the aura and the BOLD signal change [2]. During migraine aura some neuroimaging studies demonstrated reduction in cerebral blood flow (CBF) that is not sufficient magnitude to cause ischemia and is termed "oligaemia" [3][4][5]. The oligaemia starts before the onset of aura and extends into the headache phase outlasting the aura symptoms [5][6][7].…”
Section: Introductionmentioning
confidence: 99%